Legal protection for online consumers and online shopping self-protection practices among Malaysian higher education institution students - Muhammad Arif, Afida Mastura; Abu Bakar, Elistina; Daud, Nurul Atikaf; Osman, Syuhaily (Human Resource Management Academic Research Society, 2021)
Online shopping has shaped a new trend of getting consumer goods and services during the pandemic. However, online shopping has also recorded an increasing number of consumer complaints. Hence, this paper explores the legislative approach of consumer protection laws in protecting consumers in online transactions using a content analysis approach. The relevant provisions of several laws, including the Malaysian Consumer Protection Act, were analysed based on the current development to highlight online consumers’ legal protection. Additionally, a questionnaire survey was carried out among 400 respondents in the higher education institutions in the four zones of Peninsular Malaysia using systematic random sampling to determine the level of consumer self-protection practices in online shopping. The analysis of the laws revealed that the current consumer protection laws were inadequate in giving comprehensive protection for online consumers. The survey results demonstrate that while the overall findings show that consumers have high self-protection practices, the preventive measures and consumer redress dimension must be seriously considered since this dimension showed the lowest mean score. Therefore, the relevant ministry and NGOs should increase advocacy programs to motivate consumers to utilize the right to redress, and become empowered consumers to exercise self-protection practices.